Development of The Thematic Teachbook Based on Contextual Teaching and Learning (CTL) Class II At MI Raudlatul Ulum Glagahwero Panti - Rahmawati, Nika Hadiya; Ubaidillah, Sofwan Roif (IJIT: Indonesian Journal of Islamic Teaching, 2023)
ABSTRACT The development of thematic teaching materials that are more varied and in accordance with the daily lives of students and the environment where students live is not yet available at MI Raudlatul Ulum Glagahwero Panti, it is deemed necessary to develop contextual-based teaching materials, because they are able to provide a meaningful learning experience and involve an active role student. The objectives of developing these teaching materials are (1) to determine the validity of the contextual-based textbook with the theme "Playing in my Environment" for grade II Madrasah Ibtidaiyah Raudlatul Ulum Glagahwero Panti. (2) Knowing the effectiveness of using contextual-based textbooks on the theme “Playing in My Environment” for grade II Madrasah Ibtidaiyah Raudlatul Ulum Glagahwero Panti. This study uses the type of research development research and development ADDIE model which is divided into 5 steps, namely: 1) Analysis, 2) Design, 3 Development, 4) Implementation 5) and Evaluation. The product research subjects are experts in thematic material, design experts and linguists to test the validity of the product as well as class II students at MI Raudlatul Ulum Glagahwero. The attractiveness test used a questionnaire and the teaching material effectiveness test used the pre-test and post-test. The results of development research can be concluded that the results of material expert validation are 87.77%, linguist validation is 76%, and design expert validation is 87.69%. Based on the results of the recapitulation, the average is 83.8%. It can be concluded that CTL-based thematic teaching materials are in a very feasible criteria and can be used in the learning process. The results of the thematic textbook effectiveness test were obtained from student learning outcomes taken at the beginning before learning (pre-test) and after using textbooks (post-test). Based on the N-gain score test, it shows that the average N-gain score is 0.3172 which is included in the medium category, with a minimum N-gain score of -0.6 and a maximum score of 0.75. From the data analysis, it can be concluded that the effectiveness of CTL-based textbooks is in the moderate category to improve student learning outcomes in the thematic subject with the theme "Playing in my Environment" at Islamic Elementery SchoolGlagahwero, Panti District Keyword: Pengembangan bahan ajar tematik, Kontekstual